Study of Surface Morphology and Porosity of Composite Scaffold Nanofiber PVA/CS/HA with Electrospinning Method - Hartatiek Hartatiek; Nasikhudin Nasikhudin; Abdul Aziz Dwi Putra; Yudyanto Yudyanto (JPSE (Journal of Physical Science and Engineering), 2021)
This research aims to compose nanofibers as a scaffold material in bone tissue engineering in terms of surface morphological properties and porosity. HA nanorod was prepared by the precipitation-ultrasonication method, while the PVA/CS/HA nanofiber composites were made by the electrospinning method using a static collector. HA was characterized by using XRD and SEM-EDX, while the PVA/CS/HA nanofiber composites used FTIR and SEM. The results show that HA nanorod has a crystalline size of 10.86 nm, crystallinity level of 52.38 per cent, and Ca/P ratio of 1.70. From the SEM image shows HA nanorod width of 11.6 nm and 97.53 nm in length and some of it still in the form of HA nanoparticles. The diameter and porosity of PVA/CS/HA nanofiber with addition of 0, 10, 20 per cent HA were 275, 212, 265 nm and 72.94, 69.49, 70.81 per cent, respectively.DOI: 10.17977/um024v6i12021p026